The Effects of Age and Expertise on Product Evaluations: Does the Type of Information Matter? - Wang, Jing; Cole, Catherine A. (Management Science, 2016)
To better understand two large consumer segments, the boomers and the echo-boomers, we examine whether and why experts and novices from these two segments rely on attribute versus benefit information in product evaluations. In four studies, we show that expertise affects younger consumers, such that younger novices evaluate products more favorably when the descriptions feature benefit information, whereas younger experts evaluate products more favorably when the descriptions feature attribute information. However, both older novices and experts evaluate products described with benefit information more favorably than those described with attribute information. We further show that differences in the perceived diagnosticity of different types of information mediate the effects of expertise and age on product evaluations. We theorize that age differences in perceived diagnosticity occur because older and younger consumers spontaneously construe information in different ways. Therefore, age differences in the effect of expertise on evaluations should disappear when construal levels are controlled. Consistent with our hypotheses, we demonstrate that when primed to construe information at concrete levels, older consumers behave just like younger consumers—older experts formed more favorable evaluations toward products described with attribute information, but older novices formed more favorable evaluations toward products described with benefit information. When younger consumers are primed to construe information at abstract levels, they prefer products described with benefit information regardless of expertise, just like older consumers. We discuss the implications of our results for both researchers and practitioners. This paper was accepted by Pradeep Chintagunta, marketing.